KINERJA SUB DAERAH ALIRAN SUNGAI DELI BERDASARKAN ASPEK LINGKUNGAN (Performance of Deli Sub-Watershed Based on aspects of Environmental Sustainability) - Rio Haganta Ginting; Sumono Sumono; Achwil Putra Munir (Universitas Sumatera Utara, 2018)
ABSTRACT Deli Sub-Watershed is one of the Sub-Watershed of the Deli Watershed located at the upstream, midlestream and downstream and has an area of 6,522 hectares,highly vulnerable to flooding because it has an utilization area. This study was aimed to determine the performance of the sub-watershed Deli based on aspects of environmental sustainability. The parameters analyzed were the percentage of critical land, the percentage of vegetation cover, erosion index, the coefficient of the flow regime, the annual flow coefficient, sediment load, flood frequency, water usage index, protected areas and cultivation area. From this study, very low grade was included: the percentage of vegetation cover 7.16%, the flow regime coefficient 3.141, sediment load 3.907 ton/ha.year, water usage index 299.91 m3/year.people, cultivated area 100 %. Normal grade was included: protected areas30.48 %. High grade was included: the erosion index 1.656, the annual flow coefficient 0.426. Very high grade was included: critical land 67.11%, frequency of floods was more than once a year. Based on these results the carrying capacity of the river basin of sub-watershedDeli wasclassified (based on aspects of environmental sustainability) in the bad category with a total score of 84.75. Keywords: Deli sub watershed, performance, aspects of environmentalsustainability ABSTRAK Sub DAS Deli terletak dibagian hulu, tengah dan hilir yang mempunyai luas sebesar 6.522 Ha, sangat rentan terhadap masalah banjir karena merupakan daerah pemanfaatan. Penelitian ini bertujuan untuk mengetahui kinerja Sub DAS Deli berdasarkan aspek kelestarian lingkungan.Parameter yang dianalisis adalah persentase lahan kritis, persentase penutupan vegetasi, indeks erosi, koefisien regim aliran, koefisien aliran tahunan, muatan sedimen, frekuensi banjir, indeks penggunaan air, kawasan lindung dan kawasan budidaya. Dari penelitian ini yang termasuk dalam kelas sangat rendah yaitu: nilai persentase penutupan vegetasi 7,16%, koefisien regim aliran 3,141, muatan sedimen 3,907 ton/ha.thn, indeks penggunaan air 299,91 m3/thn.jiwa, kawasan budidaya 100%. Kelas sedang yaitu:kawasan lindung 30,48 %. Kelas tinggi yaitu: indeks erosi 1,656, koefisien aliran tahunan 0,426. Kelas sangat tinggi, yaitu: persentase lahan kritis 67,11%, frekuensi banjir lebih dari sekali dalam setahun. Berdasarkan hasil ini daya dukung DAS Sub DAS Deli berdasarkan aspek kelestarian lingkungan diklasifikasikan dalam kategori buruk dengan total skor 84,75. Kata Kunci: Sub DAS Deli, kinerja, aspek kelestarian lingkungan